Implementation of Good Corporate Governance and Financial Performance: Lessons from Telecommunication and Technology Sector in South East Asia - Didi Achjari; Sri Suryaningsum; Ratna Candra Sari (The Indonesian Journal of Accounting Research, 2013)
Implementation of Good Corporate Governance (GCG) has been interesting topics in Indonesia as well as in many other countries. The current study aims to investigate GCG implementation especially in communication and technology companies in ASEAN countries. GCG implementation is measured using some surrogates such as corporate action, GCG elements in organization structure, public ownership, audited financial report, and return of total assets. Samples used in this study are technology and telecommunication companies from six ASEAN countries. Data obtained from OSIRIS database from year 2005 to 2007 is examined using regression analysis. The study finds factors influencing net profit vary across the countries. In Indonesia, public ownership and corporate action affect net profit. In Malaysia, the influencing factors are corporate action, public ownership independence, quality of audited financial report, and return of total assets. Meanwhile, in Singapore the significant factors are corporate action, public ownership independence, and return of total assets. Further, Thailand's results show that all variables are significant. However, Philippine's results suggest that not all variables are significant. Lastly, in Vietnam, corporate actions, the number of GCG members and return of total assets influence the net profit.